Modelling generation Z tourists' social responsibility toward environmentally responsible behaviour: the role of eco-travel cravings - Chang, Jennifer Yee-Shan; Lim, Xin-Jean; Luo, Xi; Cheah, Jun-Hwa; Morrison, Alastair M.; Hall, C. Michael (John Wiley and Sons Ltd, 2024)
Generation Z (Gen Z) is believed to be more socially and environmentally committed. While environmentally responsible behaviour is crucial to the success of sustainable tourism, little is known about Gen Z's specific environmental behaviours in tourism settings. In this research, the roles of Gen Z's consumption emotions and environmentally friendly behaviour were explored based on cognitive appraisal and elaborated intrusion theories. The moderation impact of eco-travel cravings was also examined. With 336 valid responses collected from Gen Z tourists, it was found that destination social responsibility significantly impacted consumption emotions, but only positive emotions had direct effects on environmentally responsible behaviour and environmentally friendly tourism behaviour. The associations of emotions with environmentally responsible behaviour were also moderated by eco-travel cravings. The results offer theoretical and managerial implications for understanding Gen Z tourists that can help to accomplish sustainable tourism.